Do New Leaders Make a Difference? : Executive Succession and Public Policy Under Capitalism and Socialism - Bunce, Valerie (Book collections on Project MUSE., 2014)
Professor Bunce assesses the impact of changes in leadership on priorities in policy within the Soviet bloc and western democratic states during the postwar era, with particular emphasis on the Soviet Union and the United States. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions.